Impact of Organic Nutrient Management Practices on Yield Attributes and Yield of Summer Mungbean - Yadav, Sharvan Kumar; Babalad, H. B.; Sharma, S. K.; Choudhary, R. S.; Kumar, Naresh (International Journal of Bio-resource and Stress Management, 2016)
Field experiment was conducted on summer mungbean under organic nutrient management at Main Agriculture Research Station (MARS), University of Agriculture Sciences, Dharwad, Karnataka, India during summer season of 2012–2013. The experiment comprise of eighteen treatment combinations with three main plot treatments of organic manures and six sub plot of liquid organic manures. Results revealed that application of EC (1/3)+VC (1/3)+GLM (1/3) equivalent to 50 kg P2O5 with 5 t FYM ha-1 recorded significantly higher yield attributing characters like pod length, number of pods plant-1, seed weight plant-1 and 1000 seed weight (9.65 cm, 18.86, 6.85 g and 49.64 g, respectively) as compared to organics alone equivalent RDP and was on par with RDF+FYM. Among liquid organic manures foliar application of panchagavya 5% recorded significantly higher yield attributing characters as compared to other liquid organic manures but was on par with vermiwash 10% and cow urine @ 10%. Significantly higher seed yield of mungbean was recorded with application of EC(1/3)+VC (1/3)+GLM (1/3) equivalent 50 kg P2O5 with 5 t FYM ha-1 (1368 kg ha-1) as compared to (1/3)+VC (1/3)+GLM (1/3) equivalent 50 kg P2O5 alone (1258 kg ha-1) and was on par with RDF+FYM (1301 kg ha-1). Among liquid organic manures, foliar application of panchagavya 5% recorded significantly higher grain yield ha-1 (1430 kg ha-1) as compared to rest of the treatments except vermiwash 10% which was on par.